2017
DOI: 10.15252/embr.201744154
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain ketoacids secreted by glioblastoma cells via MCT 1 modulate macrophage phenotype

Abstract: Elevated amino acid catabolism is common to many cancers. Here, we show that glioblastoma are excreting large amounts of branched-chain ketoacids (BCKAs), metabolites of branched-chain amino acid (BCAA) catabolism. We show that efflux of BCKAs, as well as pyruvate, is mediated by the monocarboxylate transporter 1 (MCT1) in glioblastoma. MCT1 locates in close proximity to BCKA-generating branched-chain amino acid transaminase 1, suggesting possible functional interaction of the proteins. Using models, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 47 publications
0
92
0
Order By: Relevance
“…mTOR plays a key role in macrophages, providing a link between amino-acid availability, coupling this to growth, proliferation, and protein synthesis. Branched-chain ketoacids (BCKAs), a product of BCAA catabolism, has been shown to directly regulate macrophage function by reducing the phagocytic ability of TAMs ( 140 ). Further evidence for a role for BCAA comes from data demonstrating that BCAT1, the enzyme responsible for the first step in BCAA catabolism, regulates the metabolic reprogramming in human macrophages.…”
Section: Amino-acid Metabolismmentioning
confidence: 99%
“…mTOR plays a key role in macrophages, providing a link between amino-acid availability, coupling this to growth, proliferation, and protein synthesis. Branched-chain ketoacids (BCKAs), a product of BCAA catabolism, has been shown to directly regulate macrophage function by reducing the phagocytic ability of TAMs ( 140 ). Further evidence for a role for BCAA comes from data demonstrating that BCAT1, the enzyme responsible for the first step in BCAA catabolism, regulates the metabolic reprogramming in human macrophages.…”
Section: Amino-acid Metabolismmentioning
confidence: 99%
“…Administration of the selective BCAT1 inhibitor ERG240 (a leucine analogue) to mice resulted in reduced severity of immune-mediated inflammation in vivo, indicating that BCAT1 inhibition could also be of potential therapeutic interest [ 118 ]. A second study on the role of BCAT1 in macrophages found that glioblastoma cells secrete BCKAs via the monocarboxylate carrier 1 (MCT1) and that these BCKAs are taken up by tumor-associated macrophages [ 119 ]. BCKA uptake is potentially mediated by the MCT1 and/or MCT4 carriers, both of which are expressed in macrophages.…”
Section: Branched-chain Aminotransferasementioning
confidence: 99%
“…Through the overexpression of branched chain amino acid transaminase 1 (BCAT1), glioma tumors excrete elevated levels of branched-chain ketoacids (BCKA) through MCT1. Which influx into TAMs and blunt their phagocytic activity ( 61 ). GBM TAMs were also shown to drive T cell dysfunction through elevated expression of the ectonucleosidase CD39 that, together with CD73, induces the production of the immunosuppressive metabolite adenosine ( 48 ).…”
Section: Metabolic Remodeling Of the Gbm Tumor Microenvironmentmentioning
confidence: 99%